AuPd bimetallic nanoparticles decorated Cd0.5Zn0.5S photocatalysts with enhanced visible-light photocatalytic H2 production activity. (7th September 2016) - Wu, Linen; Gong, Jie; Ge, Lei; Han, Changcun; Fang, Siman; Xin, Yongji; Li, Yujing; Lu, Yan
Abstract: In this study, novel AuPd bimetallic co-catalyst decorated Cd0.5 Zn0.5 S photocatalyst was successfully synthesized via an in-situ chemical deposition method. The physical as well as the photophysical properties of the as-obtained AuPd/Cd0.5 Zn0.5 S samples were characterized by X-ray diffractometry (XRD), Transmission electron microscope (TEM), UV–vis diffuse reflection spectroscopy (DRS), X-ray photoelectron spectroscopy (XPS) and surface photovoltage spectroscopy (SPV). The AuPd bimetallic co-catalysts showed dramatic photo-generated charge separation efficiency in Cd0.5 Zn0.5 S sample, and thus significantly enhance the H2 production activity under visible light irradiation. The AuPd/Cd0.5 Zn0.5 S sample with 0.5 wt% content had the highest catalytic activity, and the corresponding H2 evolution rate is 3.65 mmol g −1 h −1, which was about 12 times as that of pure Cd0.5 Zn0.5 S sample under visible light irradiation. The photocatalytic activity of the photocatalyst was stable even after 9 cycling photocatalytic experiments. A possible mechanism on the photocatalytic enhancement of AuPd NPs was systematically investigated, which can provide a novel concept for the synthesis of other desirable photocatalytic materials. Graphical abstract: Highlights: AuPd/Cd0.5 Zn0.5 S photocatalysts were synthesized via a facile method. The AuPd/Cd0.5 Zn0.5 S shows significantly enhanced H2 evolution activity. The intimate interfaces promote the charge transfer and separation. The mechanism was proposed and confirmed by SPV result.